Assessment of Organic Matter and Chlorine Levels in Watu Kenong Coastal Waters, Situbondo - Pahlewi, Anita Diah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The coastal area that has potential natural resources both tourism and coral conservation in Situbondo Regency, East Java, is the coastal area in Bungatan District. In Bungatan, there are several beaches along the Pantura as marine tourism objects, one of them called Watu Kenong Beach. A case reported online in June 2025 where there was a complaint from a marine community group to local government about an extensive coral reef’s damage in Watu Kenong covering a dozen hectares area. The purpose of this study is to determine the concentration of organic matter and chlorine in Watu Kenong waters as an initial study material for evaluating the water quality of Watu Kenong waters in order to assist the research in the rehabilitation process of coral reefs. Water sampling locations are divided into 3 parts, namely location 1 at the Pasir Putih area, locations 2 and location 3 at the Watu Kenong section. Research method used is descriptive method. The value of organic matter parameters in the waters of Watu Kenong and its surroundings is in the range of 79.63 - 97.33 mg/L. The chlorine parameter value is 0.01 mg/L at 3 water sampling locations. The conclusion of this research are the organic matter has higher level that exceed the normal threshold and it can be considered as a pollution. The chlorine concentration is below the threshold so it is in good condition.